Effect of lime-bone ratio on compressive strength and void fraction of recycled green ecological concrete - Wang, Xiaoqin; Peng, Mengying; Wang, Ciyu; Khan Chowdhury, Ahmed Jalal (Technoscience Publications, 2019)
In order to study the influence of ash-aggregate ratio on compressive strength and void fraction of recycled green eco-concrete, the green eco-concrete prepared with recycled aggregate is selected in this study, which conforms to the concept of sustainable development. The effective porosity, compressive strength and permeability coefficient of concrete are studied, so as to determine the impact of different lime-aggregate ratio and water-cement ratio on recycled green ecological concrete. It is found that with the increase of the ash-bone ratio, the compressive strength decreases, and the ash-bone ratio is negatively correlated with the compressive strength. With the increase of the ash-bone ratio, the effective porosity increases, and the ash-bone ratio is positively correlated with the effective porosity. The compressive strength increases with the increase of water cement ratio. The water cement ratio is positively correlated with compressive strength, and the influence of water cement ratio on effective porosity shows a complex trend of rising first and then decreasing. This study lays a foundation for choosing suitable green ecological concrete, applies green ecological concrete to practical projects and verifies the feasibility of engineering application.